Akselerasi Pembangunan Berkelanjutan Melalui Kebijakan Anggaran Berkeadilan: Pendekatan Gender di Pemerintah Daerah - Muhammad Ihsan Ansari; Indra Basir (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
This study examines the implementation of Gender-Responsive Budgeting (GRB) as a strategy to accelerate the achievement of the Sustainable Development Goals (SDGs), particularly Goal 5 on gender equality, in Majene Regency, Indonesia. Employing a qualitative approach with policy discourse analysis, the research explores the formulation, implementation, and evaluation processes of GRB through document reviews, in-depth interviews, and source triangulation. Findings reveal that integrating the Gender Analysis Pathway (GAP) and Gender Budget Statement (GBS) into regional planning documents has driven positive shifts toward more inclusive program designs, especially in health and education sectors. However, effectiveness remains constrained by limited sex-disaggregated data, low technical capacity among officials, and weak inter-agency coordination. The novelty of this study lies in applying policy discourse analysis to uncover how GRB is interpreted and practiced locally, a perspective rarely explored in previous studies. These findings highlight the need for institutional capacity strengthening, improved data systems, and evidence-based evaluations to optimize GRB as a fiscal policy instrument for fostering inclusive, equitable, and sustainable development.